Posttraumatic Stress Disorder Symptoms in Lymphoma Patients: A Prospective Study - Camille, Claire; Dimeglio, Chloé; Yrondi, Antoine; Compaci, Gisèle; Delmas, Emmanuelle; Gauché, Mélanie; Laurent, Guy; Birmes, Philippe (Frontiers in Psychiatry, 2020)
The cancer experience may be marked by repeat traumas. The aim of our study was to assess traumatic events in patients diagnosed with lymphoma and to determine which of these contribute to the development of PTSD. Two weeks after receiving a diagnosis of lymphoma, patients were referred for an assessment of peritraumatic distress (PDI) and peritraumatic dissociation (PDEQ). Three months after the diagnosis, we recorded the following parameters: the patients’ worst experiences, the presence of PTSD symptoms (PCL), and symptoms of anxiety using the HAD and of depression using the BDI-II The study recruited 129 patients (46 years, SD=17.3); 70 (54%) men, 87 (67.5%) with Non-Hodgkin's lymphoma, and 42 with Hodgkin's lymphoma. Two weeks after the diagnosis, 49% of patients reported peritraumatic distress, and 20% peritraumatic dissociation, during being informed of the lymphoma diagnosis. Three months after the diagnosis, the severity of PTSD symptoms was evaluated. At this stage none of the patients suffered PTSD, but 29 (23%) individuals exhibited partial PTSD: 13.4% correlated it to receiving the lymphoma diagnosis, 8% to telling family members, and 1.6% to adverse effects. Peritraumatic distress and dissociation as a result of receiving a lymphoma diagnosis, as well as anxiety and a mucositis within the first 3 months post-diagnosis, were factors that were significantly associated with PTSD symptoms, accounting for 35.8% of PTSD’s variance. Clinicians should assess the impact of a number of stressors, which are risk factors for PTSD, starting from the time point of the initial lymphoma diagnosis.